Tax incidence in union models - Timo Tyrväinen (Bank of Finland, 1992)
This paper consideres three union inodels with alternative specifications of union preferences. We examine the effects of four tax parameters of interest on both wages and employment. The main results are as follows. The conjecture of irrelevance of de jure incidence appears not to hold in union models. Most of the comparative statics is a priori ambigous without certain restrictions on either union's objective function or technology. However, given the most plausible conjectures about the decisive elasticities, the results are not sensitive to the theoretical specification applied. Higher progressive income tax unambigously leads to lower wages. The effect of a higher proportional income tax is analogous to that of a sales tax and is ambigous without restrictions on the union's objective function but parameter values which can be considered as the most plausible indicate positive wage impact. Generally, the employer's payroll tax as well has an a priori ambigous effect on wages. Under plausible assumptions about technology, however, a rise in the payroll tax rate tends to decrease wages.
URN:NBN:fi:bof-201808021858
Keywords: 330